Liberalisasi Perbankan Dan Peranan Bank Asing Dalam Perbankan Di Indonesia - Ashilah, Afganovic Mujadid; Puspita, Alvianty Dwi; Putera, Alvin Persada (Technology and Economics Law Journal, 2024)
This study evaluates the impact of banking liberalization in Indonesia, particularly in relation to the presence of foreign banks, and compares the requirements for establishing foreign banks with those of other ASEAN countries. Using a doctrinal method, this study analyzes regulations and legislation, including Law No. 14 of 1967, Law No. 7 of 1994, and POJK No. 12/POJK.03/2021. The results of the study show that banking liberalization has brought significant benefits such as knowledge and technology transfer, increased competition, access to international markets, and economic stability. A concrete example is the role of foreign banks in rescuing troubled domestic banks during the 1997-1998 monetary crisis, such as Standard Chartered taking over Bank Bali. However, liberalization also poses challenges, including the potential for foreign domination that could threaten national economic sovereignty and limited access to credit for the MSME sector. A comparison with other ASEAN countries, such as Singapore, Thailand, and Malaysia, shows that Indonesia has a more lenient policy on foreign ownership, with a share ownership limit of up to 99%. This study emphasizes the importance of strict regulation and supervision to reap the benefits of liberalization while mitigating potential risks, ensuring that the presence of foreign banks contributes positively to the national economy.